Bioactive compounds and profiling of anticancer and antioxidant activities of Euphorbia paralias L. family Euphorbiaceae - Ahmed M.M. Youssef; Thabet H. Althneibat; Doaa A.M. Maaty; Tayel A. Al Hujran; Yousef M. Al-Saraireh (GarVal Editorial Ltda., 2024)
Context: Medicinal plants are considered the bases for chemical compounds that could be used therapeutically. Euphorbia paralias belongs to the family Euphorbiaceae. Some species of this family have demonstrated anticancer and antioxidant activities. However, the chemical compounds responsible for the anticancer and antioxidant activities of E. paralias have not been extensively studied. Aims: To identify chemical compounds of E. paralias that possess anticancer and antioxidant properties. Methods: Liquid chromatography/mass spectrometry (LC/MS) was employed to characterise the chemical compounds E. paralias methanolic extract. Using the MTT assay, anticancer activity was investigated. DPPH, ABTS, and FRAP tests were applied to assess the antioxidant action. Results: Several polyphenolic compounds, including phenolic acids, flavonoids, flavanols, fatty acids, terpenoids, and sterols, were identified in the extract. These compounds possess various biological activities. The cancer cell lines most affected by the E. paralias extract were PANC-1 with an IC50 of 60.1 ± 10.1 µg /mL, DLD-1 with an IC50 of 64.3 ± 17.5 µg/mL, and A549 with IC50 of 71.9 ± 9.8 µg/mL. The values of IC50 for the MCF-7 and U87 cancer cell lines were 74.6 ± 15.6 µg/mL and 121.3 ± 17.2 µg/mL, respectively. The cell line of normal HDF had an IC50 of 128.9 ± 11.7 µg/mL. ABTS and DPPH showed that the methanol extract scavenged the free radicals by 89.57% and 92.65%, respectively, compared to ascorbic acid and Trolox positive controls. The FRAP test showed that 1 mg of methanol extract was equivalent to 387.41 μM of Trolox. Conclusions: E. paralias contained various phytochemicals that may have anticancer and antioxidant activities. E. paralias may possess anticancer activity against pancreatic, colon and lung cancers, and it may also have antioxidant activity. Future research is recommended to investigate the isolated phytochemicals from E. paralias.